National suicide rates as an indicator of the effect of suicide on premature mortality - Gunnell, David J.; Middleton, Nicos (My University, 2003)
The health strategies of many nations include targets to reduce suicide rates. In several countries, because suicide rates are rising in young men but falling or unchanging in most other groups, achievement of target reductions might mask rises in potential years of life lost (PYLL). Analysis of routine mortality and census data for England and Wales, UK, shows that although age-standardised suicide rates fell by 18% (95% CI 15–21) between 1981 and 1998, the PYLL before age 65 years increased by 5% (4–6). National suicide reduction targets should focus on PYLL and overall suicide rates.
Keywords: Suicide; Redution targets; PYLL; Premature mortality